An Updated Review of Porcine Deltacoronavirus in Terms of Prevalence, Pathogenicity, Pathogenesis and Antiviral Strategy - Duan, Cong (Frontiers in Veterinary Science, 2022)
The recent experience with SARS-COV-2 has raised our alarm about the cross-species transmissibility of coronaviruses and the emergence of new coronaviruses. Knowledge of this family of viruses needs to be constantly updated. Porcine deltacoronavirus (PDCoV), a newly emerging member of the genus Deltacoronavirus in the family Coronaviridae, is a swine enteropathogen that causes diarrhea in pigs and may lead to death in severe cases. Since PDCoV diarrhea first broke out in the United States in early 2014, PDCoV has been detected in many countries, such as South Korea, Japan and China. More importantly, PDCoV can also infect species other than pigs, and infections have even been reported in children, highlighting its potential for cross-species transmission. A thorough and systematic knowledge of the epidemiology and pathogenesis of PDCoV will not only help us control PDCoV infection, but also enable us to discover the common cellular pathways and key factors of coronaviruses. In this review, we summarize the current knowledge on the prevalence, pathogenicity and infection dynamics, pathogenesis and immune evasion strategies of PDCoV. The existing anti-PDCoV strategies and corresponding mechanisms of PDCoV infection are also introduced, aiming to provide suggestions for the prevention and treatment of PDCoV and zoonotic diseases.